Philosophy & comedy : Aristophanes, logos, and erōs - Freydberg, Bernard, 1947- (Studies in Continental thought., 2008)
In Philosophy and Comedy, Bernard D. Freydberg illuminates the philosophical insights In Aristophanes' texts by presenting close readings of Clouds, Wasps, Assemblywomen, and Lysistrata, addressing their comic genius at the same time.